Utilization of Interactive Schistosomiasis Educational Media in Changing Clean and Healthy Living Behaviors to Prevent Stunting - Ahmad Erlan; Paisal Paisal; Yona Patanduk; Muhammad Firdaus; Anggri Alfira Yunita Assa; I Kadek Wartana; Veni Mornalita Kolupe; Sitti Fajrah; Niluh Desy Purnamasari; Desak Eka Susianawati; Fitri Arni (Journal of Public Health and Pharmacy, 2026)
Introduction: Schistosomiasis disease infecting humans in Indonesia is caused by the trematode worm Schistosoma japonicum type with the intermediate host being the snail Oncomelania hupensis lindoensis. Schistosomiasis can be chronic and worsen the incidence of malnutrition so that it can increase stunting in school-aged children. The aim of the research is to assess the increase in knowledge of students who have received local schistosomiasis so that they can practice clean and healthy living habits to prevent stunting in school children. Methods: The research was carried out using mixed methods, namely collecting qualitative and quantitative data. Data was obtained by in-depth interviews with key informants and focus group discussions. Results: Providing schistosomiasis subject matter to school children by measuring students' level of knowledge through pre and post-tests. Based on statistical analysis, a significant increase in students' knowledge about schistosomiasis was found with a p-value < 0.001. Conclusion: Empowering communities by integrating schistosomiasis education into the local school curriculum enhances students' understanding of the disease. It is important to continue incorporating local content about schistosomiasis so that school children remain consistent in preventing its transmission.